Relationship between isokinetic leg strength and knee frontal plane projection angle during single leg squat among male junior athletes - MSZ, Mail; Azhar, Mohd; NF, Affandi; S, Shaharudin (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2019)
injuries. However, studies on the top down kinetic chain of lower limb mechanics during dynamic motions such as single leg squat (SLS) among trained males were scarce. Objective: The objective of the study was to evaluate the relationship between isokinetic hip and knee strength and frontal plane projection angle (FPPA) of the knee joint during SLS. Methods: Thirty-two male junior athletes (twelve cyclists, ten runners and ten squash players) were screened for excessive dynamic knee valgus (DKV) prior to participation. Only those within the normal value of DKV were included. Their hip and knee isokinetic strength in sagittal plane were evaluated at 60º/s of angular velocity for both legs using dynamometer. Two dimensional knee FPPA was evaluated during SLS at 60º of knee flexion. Pearson correlation was evaluated between knee FPPA during SLS and isokinetic leg strength. Results: Correlations between knee FPPA and hip and knee isokinetic strength were not statistically significant except between knee flexion peak torque/body weight (r = -0.35, p = 0.05) and hamstring to quadriceps ratio (r = -0.39, p = 0.03) of non-dominant leg. Conclusions: Isokinetic hip and knee strength and knee FPPA during SLS was correlated only for non-dominant leg during SLS among male junior athletes. DKV during SLS may be reduced through strengthening the muscles around hip and knee joints.